1998
DOI: 10.1021/ma971308m
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Based Interpenetrating Polymer Networks (IPNs):  Synthesis and Properties

Abstract: Both “condensation” and “hydrosilylation” reactions have been successfully applied for the synthesis of silicon-based interpenetrating polymer networks (IPNs) consisting of a stable Si−O and Si−C linkage. We adopted a ladder silsesquioxane oligomer (LDS 1; commercial name, Glass Resin GR100) and a polycarbosilane (PCS) by hydrosilylation polymerization of bifunctional Si−H and Si−vinyl monomers as the two components for the IPN. The combined LDS/PCS curing system was studied to try to obtain homogeneously cure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Some organic-inorganic hybrid polymers with network structures have been developed by means of the hydrosilylation reaction of multi-functionalized crosslinking reagents containing Si-H or vinyl groups. [14][15][16][17][18][19][20][21][22][23][24] These network polymers have characteristic properties: high transparency, high thermal stability, good mechanical strength, excellent solvent resistance, low dielectric constants. In this context, the precise control of structures and the fundamental characterization of the organic-inorganic hybrid network is essential, not only to improve these properties but also to develop novel network polymers with specific features.…”
Section: Introductionmentioning
confidence: 99%
“…Some organic-inorganic hybrid polymers with network structures have been developed by means of the hydrosilylation reaction of multi-functionalized crosslinking reagents containing Si-H or vinyl groups. [14][15][16][17][18][19][20][21][22][23][24] These network polymers have characteristic properties: high transparency, high thermal stability, good mechanical strength, excellent solvent resistance, low dielectric constants. In this context, the precise control of structures and the fundamental characterization of the organic-inorganic hybrid network is essential, not only to improve these properties but also to develop novel network polymers with specific features.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, the solid-state NMR analysis suggested that the two components (LDS and PCS) independently formed the networks. 9 Now we are analyzing the structure of our Si-based IPN.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…3Ϫ8 In a previous article, the authors reported the synthesis of silicon-based interpenetrating polymer networks (IPNs) consisting of a stable Si-O and/or a Si-C linkage. 9 "Condensation" and "hydrosilylation" reactions were applied to the synthesis of silicon-based IPNs. Ladder silsesquioxane oligomer (LDS 1, commercial name: Glass Resin™ GR100) and a polycarbosilane (PCS) were used as the components of the Sibased IPN (Table I) (2) The casting method was used to prepare the Sibased IPN.…”
Section: Introductionmentioning
confidence: 99%
“…The organic-inorganic hybrid polymers have been prepared by some effective methods (Mark et al, 1995;Mascia, 1995;Novak, 1993;Provatas et al, 1997;Laine et al, 1998;Vaia et al, 1996;Sogah et al, 1999;Saegusa et al, 1991;Landry st al., 1993;Yamada et al, 1997;Chujo et al, 2003;Laine et al, 2003;Galiastsatos et al, 2001). Hydrosilylation reaction of multi-functionalized crosslinking reagents containing Si-H or vinyl group is one of the effective methods to yield the organic-inorganic network polymers containing Si (Yoshida et al, 2004(Yoshida et al, , 2001Tsumura et al, 1998Tsumura et al, , 1999Michalczyk et al, 1993;Lercher et al, 2002;Laine et al, 1998;Schaefer et al, 2003). The authors recently attained effective synthesis of organic-inorganic hybrid gels by means of a hydrosilylation reaction of cyclic siloxane or cubic silsesquioxane with ,-nonconjugated dienes.…”
Section: Introductionmentioning
confidence: 99%